Influência da piraclostrobina e atuação da enzima aconitase no controle do tempo do florescimento em Arabidopsis thaliana - Lima, Dawyson de (2023)
Flowering involves a chain of interaction between environmental aspects and endogenous signals to get the transcription of a complex gene network. In commercial plants, flowering can be both beneficial by promoting the attraction of pollinators and serving as a tool for genetic improvement, but it can also promote loss of productivity and make crop management difficult. Thus, studies that aim to understand the control of flowering are well accepted by the academic, scientific, commercial and productive community. Therefore, in the first chapter of this thesis we address a gap in the literature involving energy metabolism and flowering. In this work we gather evidence and information about the influence of tricarboxylic cycle enzymes on flowering time and the possible causes that led to altered flowering. In the second chapter, we analyzed the influence of pyraclostrobin application on the flowering time of Arabidopsis thaliana maintained in inductive (16 light/ 8 dark) and non-inductive (8 light/ 16 dark) photoperiods. For this, we evaluated the expression of genes related to flowering, gibberellin, DELLA proteins and aconitase; metabolite content and flowering time. The results of this work suggest that pyraclostrobin can promote changes in the activity of the enzyme aconitase and gibberellin genes, being able to alter the flowering time in plants. In the third chapter, we investigated the role of aconitase in flowering time in Arabidopsis thaliana maintained in inductive (16 light/ 8 dark) and non-inductive (8 light/ 16 dark) photoperiods. In this work we also evaluated the expression of genes related to flowering, gibberellin, DELLA proteins and aconitase; metabolite content and flowering time. The results of this work showed that the enzyme aconitase can promote changes in the expression of genes related to flowering and gibberellin is also able to change the time of flowering.